Psychometric properties of the readiness for return to work scale in occupational rehabilitation in South Korea - Jeong-Eun Lee; Soohyun Kim; Gain Shin; Su Bin Yoo; Ja-Ho Leigh (BMC, 2023)
Abstract Background This study validated the Korean version of the Readiness to Return to Work (RRTW) scale, as an assessment measure, following a musculoskeletal, work-related injury and as a measure of following return to work. Methods The participants of this study were workers with experience in rehabilitation programs at the Workers' Compensation and Welfare Service (KCOMWEL) Hospital in Korea. Factor analyses were employed to ensure the validity and reliability of the RRTW scale in claimants who were in treatment without working (the not-working group) or who had already returned to work (the working group). To test structural validity, we analyzed exploratory factor analysis (EFA) respectively for the not working group (exploratory factor analysis (EFA) (n = 200), confirmatory factor analysis (CFA) (n = 109), and the working group (n = 123). To verify concurrent validity (multidimensional and assignment approach), the variables that were identified as relevant variables in previous studies were analyzed. Results The not working group EFA, as shown in the original scale, had four dimensions, and one item was deleted: (1) Precontemplation (PC), (2) Contemplation (C), (3) Prepared for Action-Self-evaluative (PAS), and (4) Prepared for Action-Behavioral (PAB). The CFA revealed that a good model fit and reliability were suitable. Regarding the working group of EFA, it appeared in two dimensions as in the original scale, one item was modified from the UM scale to the PM scale, and the reliability was appropriate. Concurrent validity was satisfied based on the correlation between the RRTW factor and related variables. Conclusions RRTW in the Korean version of the instrument was similar to those reported for the original scale, indicating that it may be used in research and clinical settings.